TECHNICAL EFFICIENCIES OF POULTRY TOLL FEED MILLS IN KADUNA AND PLATEAU STATES, NIGERIA - Magaji Abdullahi, Aliyu; Yusuf, O.; Ammani, A. A.; Sani, I.; Angara, U. A. (FUDMA JOURNAL OF SCIENCES, 2022)
This study investigated the technical efficiencies of poultry feed firms in Kaduna and Plateau States, Nigeria. Primary data were collected using a structured questionnaire from a sample of 51 poultry feed firms, analyzed using descriptive statistics and stochastic frontier technical efficiency function. The findings indicate that poultry feed firms have an average production capacity of 4.2 tonnes per day, operating on an average of 5 days per week using not more than 1 shift per day. The feed mills were found to be technically inefficient with mean technical efficiency of 0.67. The determinants of technical efficiency were found to be operating capacity, distance to major market, number of employees, and availability of ingredients in required quantity as well as ownership type. The high cost and adulteration of ingredients, low patronage, and high competition from larger firms amongst others were factors identified as constraints to efficient poultry feed production. The study recommends that the firms should improve on the deployment of labour as well as improved wages, outsource for cheaper inputs or buy input in group to derive economies of scale and also increase their production in other to potentially maximize output.